The composition and function of the gut microbiota of Francois’ langurs (Trachypithecus francoisi) depend on the environment and diet - Sun, Yue; Yu, Yanze; Wu, Ankang; Zhang, Chao; Liu, Xun; Qian, Changjiang; Li, Jianfeng; Ran, Jingcheng (Frontiers in Microbiology, 2023)
The microbiota is essential for extraction of energy and nutrition from plantbased diets and may have facilitated primate adaptation to new dietary niches in response to rapid environmental shifts. In this study, metagenomic sequencing technology was used to analyse the compositional structure and functional differences of the gut microbial community of francois' langurs (Trachypithecus francoisi) under different environmental and dietary conditions. The results showed that in terms of the composition of the gut microbial community, there were significant differences among the gut microbiota of francois' langurs (anthropogenic disturbed populations, wild populations, and captive populations) under different environmental and dietary conditions. The microbial communities with the highest abundance in francois' langurs were Firmicutes and Bacteroidetes. Firmicutes was most abundant in anthropogenic disturbed francois' langurs and the least abundant in captive francois' langurs.Bacteroidetes abundance was highest in captive francois' langurs. In the analysis and comparison of alpha diversity, the diversity of the gut microbiota of francois' langurs affected by anthropogenic disturbance was the highest. The significant differences in gut microbiota between francois' langurs in different environments and with different diets were further supported by principal coordinate analysis (PCoA), with the disturbance group having a gut microbiota more similar to the wild group. Kyoto Encyclopedia of Genes and Genomes (KEGG) functional annotation analysis indicated a high abundance of functional genes involved in carbohydrate metabolism, amino acid metabolism, replication and repair, cofactor and vitamin metabolism, and other amino acid metabolism pathways. Additionally, the functional genes involved in carbohydrate metabolism pathways were significantly enriched in the gut microbial community of francois' langurs that were anthropogenic disturbed and captive. The gut microbiota of the francois' langurs exhibited potential plasticity for dietary flexibility, and long-term food availability in captive populations leads to changes in gut microbiota composition and function. This study explored the composition and function of the gut microbiota of francois' langurs and provided a scientific basis for understanding the physiological and health status of francois' langurs, effectively protecting the population of wild francois' langurs and reintroducing captive francois' langurs into the wild.